Heterogeneous GAD65 Expression in Subtypes of GABAergic Neurons Across Layers of the Cerebral Cortex and Hippocampus - Kajita, Yuki; Mushiake, Hajime (Frontiers in Behavioral Neuroscience, 2021)
Gamma-aminobutyric acid (GABA), a major inhibitory transmitter in the central nervous system, is synthesised via either of two enzyme isoforms, GAD65 or GAD67. GAD65 is synthesised in the soma but functions at synaptic terminals in an activity-dependent manner, playing a distinct role in excitatory-inhibitory balance. However, the extent to which each GABAergic subtype expresses GAD65 in the resting state remains unclear. In this study, we compared GAD65 expression among six GABAergic subtypes: NPY+, nNOS+, PV+, SOM+, CR+ and CCK+. According to the results, the GABAergic subtypes were classified into two groups per region based on GAD65 expression levels: high-expression (NPY+ and nNOS+) and low-expression groups (PV+, SOM+, CR+ and CCK+) in the cerebral cortex and high-expression (NPY+, nNOS+ and CCK+) and low-expression groups (PV+, SOM+ and CR+) in the hippocampus. Moreover, these expression patterns revealed a distinct laminar distribution in the cerebral cortex and hippocampus. To investigate the extent of GAD65 transport from the soma to synaptic terminals, we examined GAD65 expression in colchicine-treated rats in which GAD65 was synthesised in the soma but not transported to terminals. We found a significant positive correlation in GAD65 expression across subtypes between colchicine-treated and control rats. In summary, each GABAergic subtype exhibits a distinct GAD65 expression pattern across layers of the cerebral cortex and hippocampus. In addition, the level of GAD65 expression in the soma can be used as a proxy for the amount of GAD65 in the cytoplasm. These findings suggest that exploration of the distinct profiles of GAD65 expression among GABAergic subtypes could clarify the roles that GABAergic subtypes play in maintaining the excitatory-inhibitory balance.